EFEK EKSTRAK DAUN KEMANGI (Ocimum basilicum L.) TERHADAP KADAR HIGH-DENSITY LIPOPROTEIN TIKUS (Rattus norvegicus) MODEL ATEROSKLEROSIS - Mazara, Fitria; Mahata, Liganda Endo; Kadri, Husnil; Putri, Biomechy Oktomalio; Ali, Hirowati; Khaira, Fathiyyatul; Rusjdi, Dina Arfiani (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Atherosclerosis is the cardiovascular disease’s main pathological mechanism. Basil leaves are food companion that s widely consumed by Indonesians and contains phenolic and flavonoid bioactive compounds that can increase HDL levels. The purpose of this study was to see the effect of basil leaves extract (Ocimum basilicum L.) on HDL levels in atherosclerosis model rat. This study was conducted using the post test only control group design method on 29 rats. The rats were divided into 5 groups, K-, K+, P1, P2, and P3. K- is group of rats without treatment. K+ was treated with partial carotid ligation (PCL) and high fat diet (HFD), P1 was treated with PCL, HFD and given a dose of 100 mg/kgB basil leaves extract, P2 was treated with PCL, HFD and given a dose of 200 mg/kgBB basil leaves extract, P3 was treated with PCL, HFD and given simvastatin 1.5 mg/rat/day. HFD was given for 7 days, basil leaves extract and simvastatin given for 14 days using oral feeding tube. HDL levels tested with CHOD-PAP method using a microlab 300 spectrophotometer. The result from this study were analyzed by Saphiro-Wilk test, and Kruskal-Wallis test. The mean HDL levels obtained in the K- group were 52,65(49,70‒68.10) mg/dL, K+ 49,67±8,77 mg/dL, P1 52.70±1.58 mg/dL, P2 54.40±9.94 mg/dL, P3 58,05 ±5,34 mg/dL. The results showed there was a non-significant increase in HDL levels (p=0.377) in atherosclerosis model rat by giving basil leaves extract on both dose, and simvastatin.